Educational and Presentation Centre Natura SMŽ and Ceramic Studio Petrinja - Škorvaga, Ivica; Baltić, Laura; Bubnjić, Jelena; Bečeheli, Nikolina (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
The Natura SMŽ education and presentation centre and the Ceramic Studio Petrinja are two key projects in Sisak-Moslavina County promoting nature conservation, wildlife protection, and cultural heritage. These initiatives enrich the region’s tourism offer and raise awareness of environmental protection, tradition preservation, and sustainable development. Natura SMŽ combines technology and nature, offering visitors a deeper understanding of local flora and fauna through virtual reality (VR) and interactive experiences. Its programmes focus on children and youth, fostering environmental education and awareness. The Ceramic Studio Petrinja preserves the area’s rich pottery tradition, providing creative opportunities for all ages through workshops and hands-on ceramic production. Together, these projects strengthen the connection between people, nature, and cultural heritage. They contribute to sustainable tourism and community development by engaging visitors in innovative and educational activities that celebrate both natural and cultural values.